Institutions, policies and growth in Europe: quality versus stability - Berggren, Niclas; Bergh, Andreas; Bjornskov, Christian (Stockholm, 2013)
"Respect for human rights is a value upon which the European Union is founded, and a precondition for an aspirant state to be considered as a candidate for membership. Contrasting the fundamental rights discourse developing in the EU enlargement context and the situation within the EU, this European Policy Analysis shows the recurrent distortion between internal and external EU fundamental rights regimes, and sheds light on the on-going discussion to find ways of addressing it."